Bilingual Aesthetics A New Sentimental Education - Sommer, Doris (Public planet books, 2004)
Knowing a second language entails some unease; it requires a willingness to make mistakes and work through misunderstandings. The renowned literary scholar Doris Sommer argues that feeling funny is good for you, and for society. In Bilingual Aesthetics Sommer invites readers to make mischief with meaning, to play games with language, and to allow errors to stimulate new ways of thinking. Today's global world has outgrown any one-to-one correlation between a people and a language; liberal democracies can either encourage difference or stifle it through exclusionary policies. Bilingual Aesthetics is Sommer's passionate call for citizens and officials to cultivate difference and to realize that the precarious points of contact resulting from mismatches between languages, codes, and cultures are the lifeblood of democracy, as well as the stimulus for aesthetics and philosophy.Sommer encourages readers to entertain the creative possibilities inherent in multilingualism. With her characteristic wit and love of language, she focuses on humor-particularly bilingual jokes-as the place where tensions between and within cultures are played out. She draws on thinking about humor and language by a range of philosophers and others, including Sigmund Freud, Immanuel Kant, Ludwig Wittgenstein, Hannah Arendt, and Mikhail Bakhtin. In declaring the merits of allowing for crossed signals, Sommer sends a clear message: Making room for more than one language is about value added, not about remediation. It is an expression of love for a contingent and changing world